Anterior cervical surgery for the treatment of cervigonenic headache caused by cervical spondylosis - Fadhil; Yunus Kuntawi Aji; Sabri; Muhammad Deni Nasution; Nindi Lizen (Romanian Neurosurgery, 2024)
Cervicogenic headache (CEH) is a common disorder with cervical spine-specific nociceptive headache symptoms. Cervicogenic headaches have been studied for years, but diagnosis and treatment are continually evolving. Due to non-specific criteria and its relationship with cervical degenerative illness, diagnosis may be underestimated. In many situations, it contributes to myelopathy or radiculopathy. Local anaesthetic blocks are used to confirm the diagnosis, however, non-invasive methods are being explored. Identifying the nociceptive origin improves pain management. Physical therapy and percutaneous interventional procedures are used to treat isolated CEH. However, cervical decompression and/or fusion are often performed in situations of cervical myelopathy and/or radiculopathy. Here we report a 57-year-old female with cervicogenic headache treated with anterior lower cervical discectomy to relieve cervical myelopathy and/or radiculopathy headaches.